Демон ревности: роман : [в 2 томах : перевод с французского] (Жюльетта Бенцони) - Бенцони Жюльетта (2011)
Экземпляры: ф.23 (20171128) / Инвентарный номер: 57951 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Б 46 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44